Prevalence of symptoms and quality of life of cancer patients - Marina de Góes Salvetti; Caroline Silva Pereira Machado; Suzana Cristina Teixeira Donato; Adriana Marques da Silva
ABSTRACT Objectives: to analyze the prevalence of symptoms and their relationship with the quality of life of cancer patients. Methods: this is a cross-sectional study with 107 patients evaluated using a sociodemographic instrument, the hospital anxiety and depression scale (HADS) and the quality of life scale (EORTC-QLQ-C30). Pearson's correlation test was used to evaluate the relationship between symptoms and quality of life. Results: prevalence of female patients (56.1%), 55 years as the mean age and 10 years of schooling. Fatigue (76.6%), insomnia (47.7%), pain (42.1%), loss of appetite (37.4%), anxiety (31.8%) and depression (21.5%) were identified. Anxiety and depression symptoms presented a negative correlation with quality of life and positive correlation with physical symptoms. Conclusions: fatigue, insomnia, pain and loss of appetite were the most common and most intense symptoms. Anxiety and depression symptoms presented a negative correlation with quality of life and positive correlation with physical symptoms.